Involvement in shared decision-making for patients in public specialist outpatient clinics in Hong Kong - Xu, Richard H (Patient Prefer Adherence, 2017)
OBJECTIVE: This study is a preliminary exploration of the association between patient involvement in decision-making and patient socioeconomic characteristics and experience in specialist outpatient clinics (SOPCs) in Hong Kong. METHODS: Cross-sectional telephone interviews were conducted using the Specialist Outpatient Experience Questionnaire (SOPEQ) in 26 Hospital Authority public SOPCs in Hong Kong. The SOPEQ was designed by The School of Public Health and Primary Care at The Chinese University of Hong Kong, fully taking into account both literature review and the local context of the public specialist outpatient system in Hong Kong. A total of 22,525 eligible participants were recruited for the study. RESULTS: There were 13,966 valid responses. The results indicated that the patients who had more involvement in decision-making were younger (odds ratio [OR] =2.10; 95% CI 1.75, 2.53), more highly educated (OR =1.67; 95% CI 1.45, 1.93), less likely to be receiving a government allowance (OR =0.61; 95% CI 0.57, 0.65), and less likely to be in the new case group (OR =0.84; 95% CI 0.78, 0.92). Participants living with their families (OR =3.38; 95% CI 2.03, 5.63) or who were unemployed (OR =1.10; 95% CI 1.01, 1.21) had a more decisive role in the decision- making process. Those participants who had been more involved in decision-making and wanted to continue being more involved had greater levels of satisfaction (mean =7.94; P<0.001) and a better health status (OR =0.49; 95% CI 0.41, 0.58). CONCLUSION: Engaging patients in their health care management remains a challenge in improving patient-centered care. Our results suggest that patient engagement is associated with perceived health status and the experience of using a health service. Understanding patients’ characteristics and roles facilitates the development of preferred styles in the decision-making model.